Antimicrobial Susceptibility of Salmonella typhi and paratyphi among Pediatric Population at Tertiary Care Center of North Delhi: A Retrospective Study - Shekhar Biswas; Sulagna Tripathy; Arvind Kumar; Sanjay Chattree (Pediatric Infectious Disease)
Background: Enteric fever continues to impact millions of children who lack adequate access to clean water and sanitation. Enteric fever remains a major concern in India with an estimated incidence from hospital surveillance ranging from 12 to 1,622 cases per 100,000 child-years among children between the ages of 6 months and 14 years, and from 108 to 970 cases per 100,000 person-years among those who are 15 years of age or older. With the inappropriate use of antibiotics and rising trends of multidrug-resistant (MDR) and extensively drug-resistant (XDR) typhoid, it is becoming a public health emergency. This study evaluated the current trends in antibiotic susceptibilities to Salmonella typhi and paratyphi A and B in North Delhi. Materials and methods: We undertook a retrospective, cross-sectional multicentric study by reviewing hospital-based laboratory records of pediatric patients (up to age 18 years) whose blood culture samples were submitted from the outpatient and inpatient departments to the laboratories of Jaipur Golden Hospital in Rohini and Fortis Hospital in Shalimar Bagh, Delhi, India from September 2022 to September 2023. Results: There were 121 (75.15%) children with S. typhi and 40 (24.84%) with S. paratyphi isolates. The median age of patients was 8 years with male and female patients constituting 61.4 and 38.5%, respectively. The disease was prevalent throughout the year with high prevalence between March and May. There were four cases of MDR typhoid (2.4%) and two cases of XDR typhoid (1.2%). Conclusion: S. typhi was the predominant serotype. The study also shows that infection with S. paratyphi is not distant second as it contributes for significant 25% of total enteric fever infection. Alarming multiple drug resistance patterns were not observed. Third-generation cephalosporins as monotherapy are quite effective, and there is no need of adding azithromycin in combination form. Effective mass vaccination strategy against typhoid and water and safe hygiene (WASH) practices can decrease the burden of this disease. Broad-spectrum vaccine to cover both S. typhi and S. paratyphi is need of the hour.